THE USE OF SCHEMA ACTIVATION STRATEGY FOR TEACHING READING COMPREHENSION IN EFL CONTEXTS: A META-ANALYSIS STUDY - Lucia Monica; Endang Susilawati; Dwi Riyanti (Language and Education Journal, 2023)
This study aims to analyze journal articles that focus on the use of schema activation strategies for reading comprehension in EFL contexts. This study applied a quantitative approach and meta-analysis, by analyzing the content of the four selected journal articles in terms of the application schema activation strategy reading in national and international journal articles with meta-analysis technique it is enabled and combines a wide range of pre-existing research results, meta-analysis is a secondary data by collecting from the data or document to analyze. The result finding shows, that the researchers used different types. Two journals applied the types of formal and content schema, the others used three types of schema, there were linguistic, content, and formal schema. According to the findings of this study, teachers and researchers can use the schema activation technique to improve reading comprehension. As an alternative strategy for teaching reading comprehension